Adenoma detection in patients undergoing a comprehensive colonoscopy screening. (20th April 2013) - Raju, Gottumukkala S.; Vadyala, Vikram; Slack, Rebecca; Krishna, Somashekar G.; Ross, William A.; Lynch, Patrick M.; Bresalier, Robert S.; Hawk, Ernest; Stroehlein, John R.
Abstract Measures shown to improve the adenoma detection during colonoscopy (excellent bowel preparation, cecal intubation, cap fitted colonoscope to examine behind folds, patient position change to optimize colon distention, trained endoscopy team focusing on detection of subtle flat lesions, and incorporation of optimum endoscopic examination with adequate withdrawal time) are applicable to clinical practice and, if incorporated are projected to facilitate comprehensive colonoscopy screening program for colon cancer prevention. To determine adenoma and serrated polyp detection rate under conditions designed to optimize quality parameters for comprehensive screening colonoscopy. Retrospective analysis of data obtained from a comprehensive colon cancer screening program designed to optimize quality parameters. Academic medical center. Three hundred and forty‐three patients between the ages of 50 years and 75 years who underwent first screening colonoscopy between 2009 and 2011 among 535 consecutive patients undergoing colonoscopy. Comprehensive colonoscopy screening program was utilized to screen all patients. Cecal intubation was successful in 98.8% of patients. The Boston Bowel Preparation Scale for quality of colonoscopy was 8.97 (95% confidence interval [CI]; 8.94, 9.00). The rate of adenoma detection was 60% and serrated lesion (defined as serrated adenomas or hyperplastic polyps proximal to the splenic flexure) detection was 23%. The rate of precancerous lesion detection (adenomas and serrated lesions) was 66%. The mean number of adenomas per screening procedure was 1.4 (1.2, 1.6) and the mean number of precancerous lesions (adenomas or serrated lesions) per screening procedure was 1.6 (1.4, 1.8). Retrospective study and single endoscopist experience. A comprehensive colonoscopy screening program results in high‐quality screening with high detection of adenomas, advanced adenomas, serrated adenomas, and multiple adenomas.